Timing of the rut in fallow deer Dama dama - Kindbladh, Nathalie (SLU/Dept. of Ecology, 2015)
The timing of the fallow deer Dama dama rut was determined by investigating the time of ovulation and rut excursions in a free ranging population at the Koberg estate, in south‐western Sweden. Various factors (body mass, body condition, age and population density) that might determine the time of ovulation were included in the analyses. Ovulation data was collected from 1705 animals (adults, sub adults, senescent), shot in the years 2006-2015. GPS-positions from 21 collared females were also analysed. Half of the does ovulated before October 30 while the mean rut excursion date was October 21. Age class and population density were factors that significantly affected the yearly variation in ovulation date and individual body mass was only affecting sub adult ovulation. Bone marrow fat content showed no significant relationship with the probability to ovulate in any age class. The probability to ovulate was not affected by lactation. Probably because lactating females to a high extent consisted of prime aged females, who were able to buffer against the cost of repeated annual reproduction. Swedish law imply a break in the hunting season, with the purpose to avoid hunting related disturbance during the rut. It was found that the break was protecting close to 28% of the female population in Koberg from such disturbance during their ovulation.